Improvement of oxide ceramic materials via cation substitution for thermionic emission applications: connecting cation characteristics to changes in atomistic structure and properties - Fisher, Liam Eugene, author; Ma, Kaka, advisor; Weinberger, Chris, committee member; Neilson, Jamie, committee member; Bandhauer, Todd, committee member (Colorado State University. Libraries, 2025)
My research aimed to improve oxide ceramic materials for thermionic emission applications through strategic cation substitution, focusing on enhancing material properties like thermal stability and electrical conductivity. In thermionic emission applications, low work functions and high thermal resilience are essential material properties for efficient electron emission under high temperatures. Two oxide-based material systems, mayenite electride and strontium vanadate, were selected in the present work, because of their promising low work function, reasonable thermal stability, and economical costs of precursors. But both materials require improvements to realize or increase their applicability in thermionic emission technologies. Moreover, these two material systems possess distinguishing lattice structures from each other and utilize different mechanisms for low work function. Thus, in-parallel investigation into and comparison of the results from these two types of oxide ceramics provide fundamental insights into the interplay between the atomistic structure and cationic substitution. A critical objective of this research is to discover how various cation substitutions affect the lattice structure and how these structural changes subsequently modify key material properties for the thermionic emission application. Different cations were substituted at select sites in mayenite electride and strontium vanadate structures, individually and in dual combinations, to assess their effects on thermal stability and electrical conductivity. The hypothesis was that substituting smaller cations at particular atomic sites might increase thermal stability by altering the lattice parameters, bonding environment, and electron density. The study also investigated how dual substitutions might synergize beneficial effects from individual cations, with a focus on combinations that can potentially balance thermal stability and electrical conductivity. To characterize structural modifications, this research employs Rietveld refinement of X-ray diffraction data to conduct detailed analysis of lattice parameter adjustments and cation disorder, providing insight into the structural intricacies induced by specific substitutions. Additionally, thermogravimetric and electrical conductivity analyses reveal trends in the change of oxidation resistance and conductivity that align with anticipated impacts of certain cations. Results suggest that substituting smaller cations into mayenite lattice significantly increases oxidation onset temperature. In strontium vanadate, substitutions at the A- and B-sites have limits to stability as the material drifts further from the ideal tolerance factor of one, with critical implications for phase stability and oxidation behavior. The calcium substitute for strontium led to a vast improvement in both thermal stability (onset of rapid oxidation increased to a temperature > 1050°C) and electrical conductivity (σ > 3000S/cm). The key findings from this work demonstrate that tailored cation substitutions can substantially improve the key properties of oxide ceramics, offering pathways for material optimization for thermionic applications in harsh environments.
Keywords: mayenite electride; strontium vanadate; cation substitution; thermionic emission; oxide ceramics